Infusing Culturally Responsive Teaching in Higher Education: Insights for Multicultural Education in Indonesia - Laela Hikmah Nurbatra; Masyhud Masyhud (Journal of Innovation in Educational and Cultural Research, 2022)
The present research examines how teachers implement Culturally Responsive Teaching (CRT) as part of multicultural education in a higher education institution. The urgency of the current research lies in the fact that teachers of the 21st century need to equip students with the necessary skills and knowledge to survive in this interconnected world. However, it was evidenced that one of the challenges in implementing multicultural education is the lack of teachers' skills to be culturally responsive. Accordingly, it is essential to highlight the implementation of Culturally Responsive Teaching in the Indonesian setting. In doing so, a qualitative case study is employed to answer the research questions. The current research involves six multicultural classroom teachers as research participants with different characteristics. To gain a depth understanding of the teachers' attitudes, the researchers employed semi-structured interviews and observation as data collection techniques. Using thematic data analysis, the results indicated nine practices that reflect the implementation of Culturally Responsive Teaching in the higher education context. The nine practices are: giving more freedom to students in selecting the familiar topic, emphasizing preserving local wisdom, celebrating different perspectives in the discussion, allowing gaining and checking students' understanding, talking personally outside the class, focusing more on positive rather than negative, being a role model, being patient, and sharing the experience.